Analysis Of The Effect Of Green Product And Corporate Social Responsibility (Csr) On Brand Loyalty Of Two Most Popular Handbody Brands With Brand Awareness As A Mediation Variable - Belva Ivana Ardiyanti; Moechammad Nasir (Dinasti International Journal of Education Management And Social Science, 2025)
The study, titled Analysis of the Influence of Green Products and Corporate Social Responsibility (CSR) on Brand Loyalty of the Two Most Popular Handbody Brands with Brand Awareness as a Mediating Variable. Examines the influence of green product attributes and CSR initiatives on brand loyalty, with brand awareness as a mediating variable. The research focuses on two popular handbody brands, Nivea and Love and Beauty Planet, which emphasize eco-friendly practices and social responsibility. Employing a quantitative explanatory research method, the study collected data from 250 respondents in the Soloraya region using a structured questionnaire. Results indicate that both green product attributes and CSR initiatives significantly enhance brand awareness, which in turn positively impacts brand loyalty. Additionally, brand awareness serves as an effective mediator between green practices, CSR, and brand loyalty, providing valuable insights for sustainable brand management strategies. These findings contribute to marketing literature and offer practical implications for enhancing customer loyalty through green marketing and CSR initiatives.